Education on drug use during Ramadan - Chilmia Nurul Fatiha; Muhammad Firdaus (Community Empowerment, 2023)
The holy Ramadan season offers the best chance to maintain a healthy lifestyle because a Muslim can control his eating habits by fasting. Fasting during Ramadan is healthy for a variety of conditions, including those that affect pregnant women, people with diabetes, kidney disease, high cholesterol, obesity, hypertension, the hormone cortisol, the immune system, people who have peptic ulcers, and people who have cancer. This community service aims to educate people about drug use during Ramadan and drug use that does not break fasting. The program's results highlight that patients comprehend facts about drug use and the kinds of medications that don't break the fast during Ramadan.